Jalan Ampang Muslim Cemetery as Kuala Lumpur’s dark tourism site: a transformative insight - Mohamed Afla, Mohamad Reza (UiTM Press, 2023)
As the first established Muslim cemetery in Kuala Lumpur, Jalan Ampang Muslim Cemetery (JAMC) holds the city’s past. Since the establishment of JAMC, the graveyard has not received much attention from the public authority, leading to its derelict state. Hence, there is a need to revive and highlight the existence of JAMC as more than a purpose of commemoration and a resting place for local celebrities, politicians, aristocrats, and royals. The study argues that this can be achieved by incorporating dark tourism at JAMC as a renewal measure. Apart from its historical significance, JAMC has also displayed an abundance of greenery within a highly urbanised area, which can attract public attention. This study evaluates the possibility of opening JAMC as a dark tourism spot based on the public’s views. Partial least squares structural equation modelling analysed data from distributed questionnaires, and based on the research findings, the respondents, to some degree, agreed with making the historical cemetery a dark tourism site. However, some respondents are concerned about accessibility and the amenities available at JAMC. The results show that the opening of this historic cemetery as a place of interest is achievable by addressing these two main issues.